2007
DOI: 10.1016/j.ejor.2006.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Improved customer choice predictions using ensemble methods

Abstract: In this paper various ensemble learning methods from machine learning and statistics are considered and applied to the customer choice modeling problem. The application of ensemble learning usually improves the prediction quality of flexible models like decision trees and thus leads to improved predictions. We give experimental results for two real-life marketing datasets using decision trees, ensemble versions of decision trees and the logistic regression model, which is a standard approach for this problem. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 19 publications
(24 reference statements)
0
30
0
4
Order By: Relevance
“…Boosting Naïve Bayes was applied to claim fraud diagnosis [31]. Studies showed that MultiBoosting performed well in the prediction of customer choice [30], the prediction of financial distress [26], and the assessment of customer credit quality [21].…”
Section: Approachmentioning
confidence: 99%
“…Boosting Naïve Bayes was applied to claim fraud diagnosis [31]. Studies showed that MultiBoosting performed well in the prediction of customer choice [30], the prediction of financial distress [26], and the assessment of customer credit quality [21].…”
Section: Approachmentioning
confidence: 99%
“…Prediction of state and performance is critical to the assurance of integrity and sustainability of many complex natural and engineering physical systems [1][2][3][4]. In the modern manufacturing enterprises, timely and frequent prediction of manufacturing system Key Performance Indicators (KPI), including throughput rates, throughput losses due to breakdowns, blocking and starving, Work In Process (WIP) levels, etc., is essential to support day-today manufacturing planning and control decisions.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is known as ensemble learning (aggregation). In spite of the underlying algorithm used, the ensemble learning technique most of the time (on average) outperforms the single learning technique, especially for prediction purposes [21]. There are many approaches of performing ensemble learning.…”
Section: Introductionmentioning
confidence: 99%